Association of recurrent aphthous stomatitis (RAS) and student stress levels towards online learning : Study cross-sectional - Majid, Alya Aqila; Riolina, Ana (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Recurrent aphthous stomatitis (RAS) is a disease that often occurs in the oral cavity. The etiology of RAS is not yet known, but several factors such as stress, systemic factors, immunity, allergies, genetics, and nutrition are often linked to trigger RAS. The purpose of this study was to examine the association between RAS and student stress levels and also show an overview of RAS predisposition factors, treatment, prevention efforts, and external factors that increase student stress towards online learning in Solo Raya (Surakarta, Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen, dan Klaten) during the Covid-19 pandemic from March 2020 to December 2021. Methods: The type of research used was a cross-sectional study with purposive sampling technique. The instrument used is an online questionnaire given to students who are undergoing online learning in Solo Raya during 2020-2021 academic year for at least 1 semester, and have experienced RAS. A closed questionnaire was given to evaluate the predisposing factors for RAS, treatment, prevention efforts, and external factors that increase student stress, while the questionnaire to assess perceived stress is the perceived stress scale 10 (PSS-10). The data obtained were then analyzed by chi-square test using SPSS 27. Results: The results showed that out of 100 respondents, there were 58 students (58%) who experienced moderate stress and 42 students (42%) with severe stress. In addition, there were 49 students (49%) experiencing RAS and 51 students (51%) not experiencing RAS in the previous month. The results of the chi-square test showed a value of correlation   p = 0,327. Conclusion: There is no relationship between RAS and the stress level of students towards online learning in Solo Raya.KEY WORDS: student, stress, recurrent aphthous stomatitis, online learning.Hubungan Stomatitis Aftosa rekuren (SAR) dan tingkat stres mahasiswa terhadap pembelajaran daringABSTRAK Pendahuluan: Stomatitis aftosa rekuren (SAR) merupakan penyakit yang sering terjadi di rongga mulut. Etiologi SAR hingga saat ini belum diketahui, namun beberapa faktor seperti faktor stres, sistemik, imunitas, alergi, genetik, dan nutrisi sering dihubungkan menjadi pemicu SAR.Tujuan penelitian mneganalisis hubungan stomatitis aftosa rekuren dan tingkat stres serta menunjukkan gambaran faktor predisposisi SAR, tindakan perawatan, tindakan pencegahan, dan faktor eksternal penambah beban stres  mahasiswa terhadap pembelajaran daring. Metode: Jenis penelitian yang digunakan adalah cross-sectional study dengan teknik purposive sampling. Instrumen yang digunakan adalah kuesioner online yang diberikan kepada mahasiswa yang menjalani pembelajaran daring pada tahun 2020-2021 minimal 1 semester, dan pernah mengalami SAR. Kuesioner tertutup diberikan untuk mengevaluasi faktor predisposisi SAR, tindakan perawatan, tindakan pencegahan, dan faktor eksternal penambah beban stress, sedangkan kuesioner untuk menilai persepsi stres adalah perceived stress scale 10 (PSS-10). Data yang diperoleh kemudian dianalisis dengan uji chi-square menggunakan SPSS 27. Hasil: Hasil penelitian menunjukkan dari 100 responden yang mengalami stres sedang sejumlah 58 mahasiswa (58%) dan stres berat sejumlah 42 mahasiswa (42%). Selain itu, terdapat 49 mahasiswa (49%) mengalami SAR dan 51 mahasiswa (51%) tidak mengalami SAR 1 pada bulan sebelumnya. Hasil uji chi-square menunjukkan nilai p sebesar 0,327. Simpulan: Tidak terdapat hubungan antara SAR dan tingkat stres mahasiswa terhadap pembelajaran daring.KATA KUNCI: mahasiswa, stres, stomatitis aftosa rekuren, pembelajaran daring.